Evaluasi Program Pelaksanaan Knowledge Sharing Materi Legal Aspects di Perumda Pasar Jaya - Tiara Putri Yudanti; Mulyadi Mulyadi; Diana Ariani (Jurnal Pembelajaran Inovatif, 2019)
This research aims to describe the program evaluation. Evaluation is needed to determine the level of implementation or success of a program by knowing the effectiveness of its component. This research used formative summative evaluation model by Michael Scriven's that focused on formative research programs. Formative evaluation is used when the program is being implemented with the aim of making improvements to the program. One of the implementations of the formative evaluation is to evaluate the Legal Aspects knowledge sharing at Perumda Pasar Jaya. Formative evaluation was used to assess the implementation of the Legal Aspects knowledge sharing program at Perumda Pasar Jaya. The method of this research is survey technique which consists of distributing questionnaires to 30 respondents participants sharing Legal Aspects and interviewing the organizers of sharing activities, the Pasar Jaya Training Center. The collected data is processed using a qualitative descriptive approach.